The Development of Digital Students Worksheets for Students Elementary School Subtheme My Blood Circulation is Healthy - Bella Indriyani; Robiatul Munajah (Bulletin of Pedagogical Research, 2022)
Education in Indonesia is more using online defenders. Sometimes many students lack interest in learning because they feel easily saturated with online learning. This article developed of digital students worksheets “subtheme my blood circulation is helathy” at Elementary School of Mangga Besar 15 Pagi West Jakarta. Hence, the material received by students is complete in accordance with the basic competencies to be achieved by using digital lks equipped with games in it as student evaluation tools. This research used Research and Development (R&D) through ADDIE development model. The results found that this digital students worksheet through 3 stages of trials to find out the feasibility of digital. In phase 1 trials get results of 91%, then stage 2 results are obtained by 85%, and phase 3 trials get results of 87%. Digital students worksheet is very feasible to be used in learning activities in class V-B Elementary School of Mangga Besar 15 Pagi West Jakarta. Keywords: Digital Students Worksheets, Development Students Worksheets, Development Worksheet